Perancangan Aplikasi Novel Visual Dengan Model MDLC - Risky Adi Surya; Samsoni (CV. Multi Kreasi Media, 2023)
Technology has now developed very rapidly, its development has led to a new and sophisticated innovation that already exists in this world. Game is one that is developing rapidly along with the development of communication and information technology. There are many different types of games, and one type of game that is quite unique is called a visual novel. Visual novels require players to read every dialogue in order to follow the storyline of the game. Reading is also one of the aspects of language skills that has a problem and gets attention in human life. The DAHLIA 11 C residential area is an area in the village of Suradita, Cisauk sub-district. This area consists of 3 rows of houses in 1 RT. There, out of the 12 children interviewed, it was found that 4 elementary school children aged 6-7 years were still not fluent in reading. Therefore, in writing this scientific paper the author decided to design a visual novel game that aims to be able to help these children who are still not fluent in reading using the Multimedia Development Life Cycle (MDLC) development model. The Python programming language is the language used in making applications.